The effects of 6 weeks of creatine monohydrate supplementation on performance measures and body composition in collegiate track and field athletes - Kirksey, B.; Stone, M. H.; Warren, B. J.; Johnson, R. L.; Sone, M.; Haff, G. G.; Williams, F. E.; Proulx, Chr. (The Journal of Strength and Conditioning Research, 1999)
Thirty-six (16 men, 20 women) collegiate track and field athletes (sprinter, jumpers, and throwers) were randomly divided into a placebo (P, n = 21) group and a creatine supplemented (C, n= 15) group. Six weeks of supplementation consisted of 0.30 g·kg1·d1 of creatine monohydrate (Crm) or a placebo. Subjects were involved in a preseason conditioning program that consisted of interval sprinting and multijoint, large-muscle-group weight-training movements programmed in a periodized manner. Pretesting (PRE) and posttesting (POS) consisted of a 7-site skinfold analysis, hydrostatic weighing, countermovement vertical jump, static vertical jump, and 5 × 10-second maximum cycle ergometer rides. Data were analyzed using G × T analysis of variance. Significant interactions occurred for several variables. Creatine effected superior gains (percent change creatine vs. placebo) in countermovement vertical jump height (7.0 vs. 2.3%), countermovement vertical jump power index (6.8 vs. 3.1%), average cycle peak power (12.8 vs. 4.8%), cycle average power (10.8 vs. 3.1%), cycle total work (10.8 vs. 3.5%), cycle initial rate of power production (30.0 vs. 11.2%), and lean body mass. These results suggest that 6 weeks of Crm intake can favorably enhance vertical jump, power output, work capacity, and lean body mass in men and women collegiate track and field athletes following a periodized training.